The impact of transportation and walkability on Residential Property Value - Nurul Wazien, Mohd Noor (2021)
This study analyzes the affect transportation and walkability toward Residential PropertyValue in neighborhoods of Shah Alam, Selangor in order to observe the impact of transportation and walkability as one of prominent smart growth principles in creating economic value. For the Residential Property Value assessment, a hedonic regression model was created to estimate median Residential Property Value in Shah Alam, Selangor based on Secondary data that colled in the Brickz.com. The result of the model shows that transportation and walkability components have weaker influence on estimated Residential Property Value compared to other Structure Characteristic of the residential like no of floor, no of bedroom and the land area. Only three variable from the Structure Characteristic were statistically significant in this study: Structure Characteristic no of floor, Structure Characteristic No of Bedroom and Structure Characteristic Land Area. Consequently, all transportation and walkability are insignificant towards residential house prices. This shows that there are still ways to increase house prices through attractive house structure planning. With this, the formation of an attractive house structure in development planning is an important aspect in increasing the demand for house prices while raising house prices efficiently. The adoption of appropriate use of public transport uses the principle of good growth to achieve added value and improve the overall quality of life in the neighborhood.